Tác động của chính sách tài khoá lên thị trường chứng khoán ở các quốc gia châu Á - Bùi Duy Tùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the impact of fiscal policy on stock price fluctuations represented by stock price indices in different Asian countries. An empirical model is constructed based on arbitrage pricing theory (APT) using macro control variables. To determine long- and short-run relations among the variables, we employ mean-group (MG) and pooled mean-group (PMG) estimators for the panel data, which show that stock prices do respond to fiscal policy changes. An implementation of expansionary fiscal policy is found to produce positive market signals, whereas maintaining a sound fiscal environment helps raise stock value on the market.
Keywords: Fiscal policy; Stock market; Asia; Pooled mean-group; Mean group